Thermo‐responsive dielectric pulse in poly(vinylidene fluoride)/polyethylene glycol fibrous mats. Issue 11 (12th September 2022) - Zhou, Weijie; Gong, Yutie; Li, Hairong; Huang, Jing; Liu, Qiongxin; Wang, Wei; Qu, Xiaoyuan; Jiang, Ming; Sun, Jiuxiao
Abstract: Thermo‐responsive dielectric materials have attracted broad attention in smart electronic device applications. Here, we present a facile one‐step fabrication technique of thermo‐responsive dielectric fibrous mats via efficient solution blow spinning of poly (vinylidene fluoride)/polyethylene glycol (PVDF/PEG). A strong room‐temperature dielectric pulse is triggered by thermally induced crystalline–amorphous phase transition of the PEG. The PVDF, serving as a host, enables the fibrous mats not only to attain solid–solid phase transition but also to spontaneously provide the self‐supportability. The dielectric pulse mechanism in PVDF/PEG based on crystalline–amorphous phase transition is clearly demonstrated. The all‐polymer dielectric pulsing composites hold great potential in next‐generation electronic engineering, exemplified by the creation of flexible, long‐service‐life, and low‐cost smart electrical devices. Abstract : We present a facile one‐step fabrication technique of thermo‐responsive dielectric fibrous mats via efficient solution blow spinning of poly (vinylidene fluoride)/polyethylene glycol. A strong room‐temperature dielectric pulse is triggered by thermally‐induced crystalline‐amorphous phase transition.